2005
DOI: 10.1101/gad.321305
|View full text |Cite
|
Sign up to set email alerts
|

The FLP proteins act as regulators of chlorophyll synthesis in response to light and plastid signals in Chlamydomonas

Abstract: [Keywords: Chlorophyll synthesis; plastid signal; light regulation; alternative splicing; Chlamydomonas] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 45 publications
1
53
0
Order By: Relevance
“…RNAi of Alb3.2 can be induced by transferring these cells progressively to higher 5-FI concentrations. The lethality is not attributable to the RNAi system used, because another RNAi strain in which the FLP gene of Chlamydomonas was silenced could be maintained indefinitely under the same conditions (Falciatore et al, 2005). Therefore, Alb3.2 seems to have an essential function in the cell.…”
Section: Reduction Of Alb32 By Rnai Leads To a Decrease Of Psii And mentioning
confidence: 91%
See 3 more Smart Citations
“…RNAi of Alb3.2 can be induced by transferring these cells progressively to higher 5-FI concentrations. The lethality is not attributable to the RNAi system used, because another RNAi strain in which the FLP gene of Chlamydomonas was silenced could be maintained indefinitely under the same conditions (Falciatore et al, 2005). Therefore, Alb3.2 seems to have an essential function in the cell.…”
Section: Reduction Of Alb32 By Rnai Leads To a Decrease Of Psii And mentioning
confidence: 91%
“…The effect is attributable specifically to the depletion of Alb3.2, because the less affected strain Alb3.2_1 and another RNAi transformant targeted for FLP (Falciatore et al, 2005) did not display this phenotype (Figure 7). Measurements of the areas of vacuoles in 21 randomly chosen cell sections revealed that the vacuolar area represented 60 and 11% of the Wild-type cells were transformed with a plasmid carrying an inverted repeat of Alb3.2 cDNA using the cosilencing system described by Rohr et al (2004).…”
Section: Reduction Of Alb32 By Rnai Leads To a Decrease Of Psii And mentioning
confidence: 99%
See 2 more Smart Citations
“…As such, it is likely that GLK gene function was required for chloroplast development in the last common ancestor of bryophytes and flowering plants. Therefore, GLK-mediated regulation of chloroplast development defines one of the most ancient conserved regulatory mechanisms identified in the plant kingdom, other notable examples being microRNA-mediated control of gene expression (Floyd and Bowman, 2004), regulation of state transitions in the chloroplast (Bellafiore et al, 2005), and protoporphyrin signaling from the chloroplast to the nucleus (Falciatore et al, 2005).…”
Section: Discussionmentioning
confidence: 99%